Asupan zat gizi, status gizi dan motivasi serta hubungannya dengan produktivitas pekerja perempuan pada bagian pencetakan di Pabrik Bakpia Pathuk 25 Yogyakarta - Rina Kusriyana; Siti Helmyati; R Dwi Budiningsari (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2010)
Background: Employees’ productivity is closely related with nutritional condition. Nutritional condition can be physically assessed by determining nutrition status. One’s nutrition status is directly influenced by nutrient intake. However, health and nutrition status of an employee in general have not got proper attention that lead to decreasing productivity. Productivity is not only influenced by nutrition status but also by psychological factor that involves motivation.Objectives: To identify association between nutrient intake, nutrition status and motivation and productivity of female workers at production department of Bakpia Pathuk 25 Factory Yogyakarta.Method: The study was a survey that used cross sectional design. Subject of the study were female workers at production department as many as 40 people taken through proportional stratified random sampling technique. Data of subject assessed were nutrient intake (energy, carbohydrate, fat, protein, and Fe), nutrition status, motivation, and productivity. Nutrient intake was assessed using food recall 24 hours within 4 days, nutrition status was specified using anthropometric approach using body mass index (weight/height), motivation was assessed through motivation questionnaire and productivity through quantity of production (raw bakpia) produced by the worker at a time observation (44 minutes for workers at crust production and 1 hour for workers at filing department) within 3 times observation.Result: The result of linear regression analysis showed that association between nutrient intake (energy, carbohydrate, fat, protein and Fe), nutrition status and productivity was r<0.25 and p>0.05 whereas between motivation and productivity was r=0.901; R2= 0.812; and p=0.000 for variables of wages, intake of energy, Fe and motivation and productivity.Conclusion: There was no significant association between nutrient intake (energy, carbohydrate, fat, protein and Fe) and nutrition status and productivity; there was signifiant association between motivation and productivity. Concurrently only motivation had significant association with productivity.